Acoustic and non-acoustic performance coal bottom ash concrete - Shahidan, Shahiron 1983- (SpringerBriefs in applied sciences and technology, 2020)
This book highlights the acoustic performance of concrete made with Coal Bottom Ash (CBA) that has contributed to environmental issues. The usage of CBA in concrete can be recommended as good concrete due to its absorption properties. This book focuses on the principles and techniques employed in acoustic design. The book first elaborates on the perception of noise and properties of noise, followed by physical data, units and measurements. Finally, it takes a look at acoustic analysis which includes acoustic performance effects using different volumes of CBA, density and porosity of concrete.